O papel da imaginação na teoria ética Rousseauniana - Gobi, Luciana Vanuza (2017)
In this study, through the analysis of the concepts of natural man and civil man present in Rousseau's theory, the central objective will be to understand what passions the author attributes to the man when he lived in the state of nature, as well as the passions that he ascribe to the men when they begin to live in society. The description of human behavior from these passions and the search for ethical parameters generate to the philosopher a criticism: they accuse him of formulating a sentimentalist ethic. We will defend here that this accusation does not proceed because the author, despite valuing concepts such as love of self, self-love and piety, uses imagination. In order to reconcile these two poles, we shall begin by exploring Rousseau's definition of love of self, this feeling is responsible for the survival instinct and the responsible for the emergence of other passions, among them the self-esteem - guilty of the corruption of man -, because it is from this feeling that conflicts and the exploitation of one individual over the other arises. However, love of love will also give rise to piety, a sentiment which is opposed to self-love insofar as it provokes the solidarity of a subject with his fellows. When we enter into this question we are faced with another problem, for Rousseau, piety is divided into three forms: natural piety, social piety and theatrical piety, and the author will defend each of these aspects in the works Discourse on the origin and basis of inequality between men, Essay on the origin of languages and Letter to D'Alembert and Writings for the Theater. Therefore, it is difficult to say whether these concepts are antagonistic - but this will be the impression in a first contact - or if they complement each other, then, in so far as man changes the state of nature by his civilian status, he exchanges that piety for another. The fact is that by admitting social piety, we admit the importance of imagination in Rousseau's ethical theory. Now, reason and feelings will associate. The discussion, finally, is about the role of the imagination in Rousseaunian ethics: does it give the security and stability that these feelings do not provide?